ASSESSING KNOWLEDGE AND ATTITUDE OF CONSUMERS TOWARDS FOOD WASTE PREVENTION - Noorazlin Ramli; Ainaa Sakinah Abdul Karim; Siti Hajar Abdullah; Fatimah Abd Ghani; Wan Nazriah Wan Nawawi (Journal of Islamic, Social, Economics and Development, 2022)
In today's world of sustainability, it is undeniable that food waste has become a major source of concern for many countries. One of the most significant sources of food waste is consumers. Thus, this study aimed to identify the level of consumers’ food waste knowledge and attitude towards food waste prevention.This study is structured through a self-administered survey with the consumers of foodservice establishments in Kuala Terengganu. With 175 respondents, the data were analysed using SPSS version 24. Descriptive analysis and correlation analysis were used to analyse the results. The findings show that knowledge and attitude have a substantial impact on a consumer's ability to prevent food waste. More research should be conducted to determine the best practices that may be implemented. Overall, when the consumer's degree of understanding rises, they will adopt a more positive attitude